Superimposed structures, incremental strain and deformation path from field data to modelling: A case study from the Alpi Apuane metamorphic core complex (NW Tuscany, Italy). - Molli, G.; Köhn, Daniel; Allacorta, L.; Danese, L.; Zampelli, S.; Zazzeri, M. (Journal of Structural Geology, 2022)
In this study, superimposed folds and antitaxial strain fringes are investigated to unravel the deformation path of the core zones of the Alpi Apuane metamorphic complex (northwest Tuscany Italy). Detailed field mapping combined with microstructural analyses is used together with computer-modelling of a complex strain fringe system to disclose the main steps of the Alpi Apuane syn-metamorphic deformation history. A comparison between natural investigated fibres and those produced by paraffine wax experiments provides details of the relative core-object-fringe rotation allowing new insight on the growth kinematics of strain fringes. The results of our analyses show that our composite fringe system is characterized by a first set of fibres to be related with the main composite axial planar foliation of regional scale isoclinal non-cylindric folds. This first set of fibre fringes records a local non-coaxial strain with an absolute core-object rotation (relative to an external reference frame represented by the main foliation) of 140° and a calculated shear strain (γ) of about 4. The second set of fringes, developed after the tilting of the main foliation and the first fringe-set in a sub-vertical orientation, records a lower absolute rotation of the core-object (25°), a lower shear strain (γ) of about 1.4 and a coaxial strain associated with the vertical shortening. This part of the composite fringe system and the related structures may relate to the switch from the crustal scale contractional regime to the extensional one, which characterized the development of the inner northern Apennines orogen.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Alpi Apuane; Modelling incremental strain; Northern Apennines; Strain fringes; Superimposed folds; Tectonics